BRINQUEDOTECA: um espaço importante no desenvolvimento e aprendizagem das crianças na educação infantil - GARCIA, Luana Alice Vieira (2024)
The Course Conclusion Paper entitled "Toy Library: An Important Space in the Development and Learning of Children in Early Childhood Education", aimed to analyze how they are developing activities in the space of the toy library with the students of a School of Early Childhood Education in the Municipality of Breves. This research proposes to answer the following questions: To identify the contribution of the toy library to the process of development and learning of children in early childhood education; to know how the pedagogical work with the children in the toy library is developed and to recognize the role of the toyist as mediator in the process of learning of the children. For its accomplishment, the qualitative approach was chosen, and the method used was the case study at a School of Early Childhood Education in the municipality of Breves-PA. The technique of data collection was performed through the semi-structured interview. Participated in the survey 03 teachers of the toy library. In order to base the discussions of this research, we use renowned authors that approach the theme in vogue such as Cunha (2007), Friedmann (1992, 2012), Kishimoto (1998, 2011), Redin (2007), Gimenes and Teixeira (2013). The results of the research indicate that the toy teachers acknowledge the importance of the toy library as a facilitating agent for development, they also recognize the importance of planning the play activities developed in this environment, however the quantity of teaching materials and the length of time children in the space of the Toy Library at the moment are not satisfactory.